2008
DOI: 10.1186/1471-2334-8-139
|View full text |Cite
|
Sign up to set email alerts
|

Differences between naive and memory T cell phenotype in Malawian and UK adolescents: a role for Cytomegalovirus?

Abstract: Background: Differences in degree of environmental exposure to antigens in early life have been hypothesized to lead to differences in immune status in individuals from different populations, which may have implications for immune responses in later years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 42 publications
5
29
2
Order By: Relevance
“…Finally, it might reflect early life environmental exposure to pathogens. This is in keeping with the differences in T cell memory subsets, especially higher numbers of T cells with an effector memory immunophenotype and lower numbers of T cells with a central memory immunophenotype, as described in Malawian as compared with UK adolescents, despite no differences in lymphocyte populations in cord blood from these populations 19. It has been suggested that these differences result from greater exposure to early-life infections in the African environment 20.…”
Section: Discussionsupporting
confidence: 82%
“…Finally, it might reflect early life environmental exposure to pathogens. This is in keeping with the differences in T cell memory subsets, especially higher numbers of T cells with an effector memory immunophenotype and lower numbers of T cells with a central memory immunophenotype, as described in Malawian as compared with UK adolescents, despite no differences in lymphocyte populations in cord blood from these populations 19. It has been suggested that these differences result from greater exposure to early-life infections in the African environment 20.…”
Section: Discussionsupporting
confidence: 82%
“…One main inducer of constant immune activation is the more frequent exposure to infectious diseases in Entebbe, which lies on the shore of Lake Victoria, when compared with the Lausanne population. Chronic or acute inflammatory conditions, including pathogenic viral, bacterial, fungal, or parasitic infections, might play a role in this immune activation (49,50). Of note, we did not observe significant differences in YF-17D NAb titers between individuals who reported a coinfection as an adverse event after vaccination and those that did not.…”
Section: Discussionmentioning
confidence: 45%
“…It has been suggested that, at least among non-HIV-infected individuals, immune responses are induced and maintained very differently in young Africans than in age-matched European controls, due to the earlier and greater exposure to antigenic challenges 18. This was true for exposure to CMV in particular and although it is not clear how this might be responsible for more resistance to the virus in the immunocompromised state, this difference in environmental exposure in early life may play a role in the putative protection against CMV retinitis among Africans.…”
Section: Resultsmentioning
confidence: 99%